Profiling the miRNA from Exosomes of Non-Pigmented Ciliary Epithelium-Derived Identifies Key Gene Targets Relevant to Primary Open-Angle Glaucoma - Padmanabhan Paranji Pattabiraman; Valeria Feinstein; Elie Beit-Yannai (MDPI AG, 2023)
Oxidative stress (OS) on tissues is a major pathological insult leading to elevated intraocular pressure (IOP) and primary open-angle glaucoma (POAG). Aqueous humor (AH) produced by the non-pigmentary ciliary epithelium (NPCE) drains out via the trabecular meshwork (TM) outflow pathway in the anterior chamber. The exosomes are major constituents of AH, and exosomes can modulate the signaling events, as well as the responses of their target TM tissue. Despite the presence of molecular mechanisms to negate OS, oxidative damage directly, as well as indirectly, influences TM health, AH drainage, and IOP. We proposed that the expression of microRNA (miRNAs) carried by exosomes in the AH can be affected by OS, and this can modulate the pathways in target cells. To assess this, we subjected NPCE to acute and chronic OS (A-OS and C-OS), enriched miRNAs, performed miRNA microarray chip analyses, and miRNA-based gene targeting pathway prediction analysis. We found that various miRNA families, including miR27, miR199, miR23, miR130b, and miR200, changed significantly. Based on pathway prediction analysis, we found that these miRNAs can regulate the genes including Nrf2, Keap1, GSK3B, and serine/threonine-protein phosphatase2A (PP2A). We propose that OS on the NPCE exosomal miRNA cargo can modulate the functionality of the TM tissue.